Non‐Tidal Ocean Loading Signals of the North and Baltic Sea From Terrestrial Gravimetry, GNSS, and High‐Resolution Modeling - C. Voigt; R. Sulzbach; H. Dobslaw; A. Weise; L. Timmen; Z. Deng; M. Reich; N. Stolarczuk; H. Peters; M. Fietz; M. Thomas; F. Flechtner (Geophysical Research Letters, 2024)
Abstract Non‐tidal ocean loading (NTOL) signals are known to be a significant source of geophysically induced noise in gravimetric and geodetic observations also far‐away from the coast and especially during extreme events such as storm surges. Operationally available corrections suffer from a low temporal and spatial resolution and reveal too small amplitudes on continental stations. Dedicated high‐resolution sea‐level modeling of the North and Baltic Sea provides an improved prediction of NTOL signals. Superconducting gravimeter and Global Navigation Satellite Systems observations on the small offshore island of Heligoland in the North Sea are used for an evaluation of the model values revealing largely increased correlations of up to 0.9 and signal reductions of up to 50% during a storm surge period of one month in January and February 2022. Evaluations on additional continental superconducting gravimeter stations also show significant improvements through the recommended high‐resolution modeling for improved signal separation further away from the coast.